ANALISIS WACANA NOVEL CITRA RASHMI - Yunita Nugraheni; Heri Dwi Santoso; Sri Winda Utami (Universitas Muhammadiyah Semarang, 2017)
This research is aimed to describe the construction of woman rebellion done by the crown princess, Citra Rashmi in the novel Citra Rashmi: Konspirasi Putri Mahkota by Tasaro GK and to describe the position of patriarchal ideology behind the woman rebellion done by the crown princess, Citra Rashmi in the novel Citra Rashmi: Konspirasi Putri Mahkota by Tasaro GK. Method used in this research was method of critical discourse analysis stated by Teun Van Dijk. The component of research included text, social cognition and social context. The result of research shows that Citra Rashmi is described as a woman with competency in martial arts. Citra Rashmi is also a crown princess of Pasundan Kingdom. The martial competency arts which had by a woman is depicted the deconstruction of physical appearance of a woman, and the breaking out of stereotype of a princess as well. In short way, the writer wants to describe the characteristic of main character that break the patriarchal ideology.